BIOLOGICAL AND ENVIRONMENTAL CHANGES IN LAKE BAIKAL DURING THE LATE QUATERNARY INFERRED FROM CARBON, NITROGEN AND SULFUR ISOTOPES - Watanabe T.; Naraoka H.; Nishimura M.; Kawai T. (My University, 2004)
An 8-m continuous sediment core, approximately 250-ky-old at the bottom, from Academician Ridge in Lake Baikal, has been analyzed for the stable isotopes of carbon, nitrogen and sulfur, in order to study the paleoclimatic and paleobiological changes that occurred in the Eurasian continental interior. These isotopic changes are closely related to changes in vertical lake-water circulation between glacial and interglacial periods. Sedimentary organic carbon in cool periods is more enriched in 13C (−23.8‰ on average) than that in warm periods (−27.0‰ on average). The 13C-enrichment of organic carbon suggests a decrease of land-derived organic matter influx to the lake, less precipitation, and loss of terrestrial vegetation around Lake Baikal in cool periods. Pyrite in high total sulfur/total organic carbon (TS/TOC) layers shows strong depletion in 34S (−20.8‰ to −32.4‰) during climate transitions from glacial to interglacial periods at the beginning of oxygen isotope stages (OIS) 1, 5 and 7. The 34S-depleted pyrite indicates augmentation of dissimilatory sulfate reduction by sulfate reducing bacteria (SRB) at the sediment–water interface. Enhancement of aqueous sulfate concentrations and limitation of oxygen circulation to the surface sediments might also occur in the climate transition periods. The δ15N values of total nitrogen increase abruptly by ∼2‰ just after the δ34S negative peaks, which may result from low nutrient concentrations in the euphotic zone associated with water circulation changes in Lake Baikal.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная